2021
DOI: 10.2147/opth.s300239
|View full text |Cite
|
Sign up to set email alerts
|

Fear Associated with COVID-19 in Patients with Neovascular Age-Related Macular Degeneration

Abstract: Purpose: Since the beginning of the COVID-19 pandemic, news related to the pandemic has created a feeling of fear, particularly among high-risk groups including elderly patients. This study aimed to assess the fear associated with COVID-19 and to evaluate the fear of vision decrease related to the delay of treatment in neovascular age-related macular degeneration patients (nAMD) during the pandemic. Patients and Methods: This is a prospective cross-sectional study of 160 actively treated patients with nAMD enr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 15 publications
(32 reference statements)
1
7
0
Order By: Relevance
“…The levels of those are modulated by a plethora of factors, among them sex and age. 25 , 37 Hence, one may expect that patients admitted for RRD surgeries during the COVID-19 pandemic had different demographic characteristics than those treated in the pre-COVID era. However, similar to previous studies, we did not find significant differences in the age and sex distribution of patients admitted during the pandemic and a year earlier.…”
Section: Discussionmentioning
confidence: 99%
“…The levels of those are modulated by a plethora of factors, among them sex and age. 25 , 37 Hence, one may expect that patients admitted for RRD surgeries during the COVID-19 pandemic had different demographic characteristics than those treated in the pre-COVID era. However, similar to previous studies, we did not find significant differences in the age and sex distribution of patients admitted during the pandemic and a year earlier.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13][14][15][16][17] Before the appointment, patient education about the safety and hygiene measures in place may alleviate fear and improve adherence. [18][19][20][21] Body temperature and screening questions regarding travel history, occupation, contact, and cluster history (TOCC) should be checked immediately before patients enter the clinic. [12][13][14][15]17,20 In addition, Carnevali et al suggested that every patient should have a nasopharyngeal swab for COVID-19 screening before treatment and only those with negative results should be allowed to receive therapy.…”
Section: For Patientsmentioning
confidence: 99%
“… 14 Previous studies had suggested that anxiety and fear associated with COVID-19 were prevalent among patients with ophthalmic disorders, affecting health-seeking behaviour. 8 , 15 However, there had been limited assessment of patient perspectives during the third national lockdown. A year has passed since the initial outbreak, and this study revealed that the fear of contracting COVID-19 is still a crucial factor that could influence patients’ willingness to attend hospital appointments.…”
Section: Discussionmentioning
confidence: 99%